2019
DOI: 10.1016/j.toxrep.2019.06.017
|View full text |Cite|
|
Sign up to set email alerts
|

Pharmacological safety of Plinia cauliflora (Mart.) Kausel in rabbits

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 57 publications
0
10
0
3
Order By: Relevance
“…The TP content ranged from 147.68 ± 2.45 to 196.63 ± 1.39 mg GAE g −1 d.w., which is higher than what has been reported in the literature. Aqueous extract of jaboticaba peels was also produced by maceration at 100 • C and pH 6 by Lequinste et al [28], who found 36.12 mg GAE g −1 d.w. Hydroethanolic extract of jaboticaba peels was produced by maceration by Meira et al [29], who obtained 47.5 mg GAE g −1 d.w. Palozi et al [30], using another extraction methodology (accelerated solvent extraction), obtained aqueous extract from jaboticaba peels with total phenolic of 181.42 ± 3.67 mg GAE g −1 d.w., which was closer to the results found in the present study. The AA of JPE was in the range of 78.61 ± 0.21% to 94.85 ± 0.09%.…”
Section: Chemical Composition and Properties Of Jpementioning
confidence: 99%
“…The TP content ranged from 147.68 ± 2.45 to 196.63 ± 1.39 mg GAE g −1 d.w., which is higher than what has been reported in the literature. Aqueous extract of jaboticaba peels was also produced by maceration at 100 • C and pH 6 by Lequinste et al [28], who found 36.12 mg GAE g −1 d.w. Hydroethanolic extract of jaboticaba peels was produced by maceration by Meira et al [29], who obtained 47.5 mg GAE g −1 d.w. Palozi et al [30], using another extraction methodology (accelerated solvent extraction), obtained aqueous extract from jaboticaba peels with total phenolic of 181.42 ± 3.67 mg GAE g −1 d.w., which was closer to the results found in the present study. The AA of JPE was in the range of 78.61 ± 0.21% to 94.85 ± 0.09%.…”
Section: Chemical Composition and Properties Of Jpementioning
confidence: 99%
“…In vivo studies were performed by Batista et al [141], who obtained an improvement in the triglyceride excretion and hepatic lipid peroxidation in rats fed a high-fat diet enriched with lyophilized jabuticaba peel. Palozi et al [142] showed that the oral use of ethanolic extracts of jabuticaba peel in rabbits did not cause significant changes in respiratory, cardiovascular, and central nervous system functions, ensuring pharmacological safety for the use of this residue. However, biological studies of jabuticaba seeds are scarce, and further research is required to assure the complete safety of these potential sources of bioactive compounds.…”
Section: Fruit By-products (Seeds): Chemical Characterization and mentioning
confidence: 99%
“…Moreover, the industrial process of this fruit generates by-products, such as peels and seeds, which have a higher phenolic content than the pulp and are normally discarded in the environment [5]. Although the peels are considered a residue, their extracts highlight their antioxidant, anti-inflammatory, and antimicrobial properties [7]. This suggests that the peel presents itself as a potential and sustainable alternative to the use of synthetic additives.…”
Section: Introductionmentioning
confidence: 99%